Performance Implementation Analysis of PT SMS Finance Padang Company Leasing - Khansa, Mutiyah; Amelia Putri, Natasya; Permata Sari, Olivia; Rafif, Rizqullah; Nila Sari, Vivi (Universitas Ibn Khaldun, 2023)
Companies in the field of leasing services are currently emerging due to the increasing public need for transportation facilities in terms of life. Globalization has an impact on business development in Indonesia, especially with the entry of multinational companies in Indonesia. This can be seen in companies that provide credit services. With increasingly competitive conditions, leasing service companies are required to really understand the dynamics of customer tastes that are their target market and how to satisfy these customers. One way is to provide quality services, both personally and in terms of ingredients, by creating a good service, customers will feel satisfied because their wants and needs have been fulfilled. Because there are so many choices that exist, it is difficult for consumers to determine which product to choose, so that consumers try to find information from the media around them (for example: print media and electronic media), the information obtained from these media will be easier to understand and easier to find. to recall. Submission of information through the media is called promotion.